Strengthening Pancasila Student Profiles Based on Culture Character in the Mobilization School Program in Mobilizing Schools in Makassar City - Muhajir Muhajir; Suardi Suardi; Sri Rahayu Pudjiastuti; Mohammad Mathuro; Abdul Latief; Kasmawati Kasmawati; Nurhikma Nurhikma; Nurfadilah Nurfadilah (JED (Jurnal Etika Demokrasi), 2023)
The problem of research is strengthening the profile of Pancasila students in driving school program schools that need to become a culture of character in driving schools. The research objective is to strengthen the profile of Pancasila students in driving schools through culture character. The research method uses mixed qualitative and quantitative research methods, namely mixed methods concurrent embedded. Informants totaling 20 informants consisting of driving school principals or driving teachers, while the research respondents totaled 50 respondents. Collection techniques through questionnaires google form, observation, interviews and documentation. Qualitative data analysis was carried out through reduction, display and drawing conclusions, while quantitative data was carried out through verification, tabulation and percentages. The results of the study show that strengthening the profile of Pancasila students through culture in driving schools at Level 1, 2 and 3 Senior High Schools in the city of Makassar is carried out through positive habits carried out by mobilizing school teachers and principals of mobilizing schools for students such as the Strengthening Project activities Pancasila Student Profile. The conclusion of this research is to strengthen the profile of Pancasila students in driving school program schools through the culture character, namely the habituation of school activities that strengthens the profile character of Pancasila students.